Comparing drug combinations for graft-versus-host disease prophylaxis using the U.S. Food and Drug Administration Adverse Event Reporting System - Toru Ogura; Chihiro Shiraishi; Aiko Urawa (Clinical Transplantation and Research, 2025)
Background : Graft-versus-host disease (GVHD) is a severe complication for transplant patients, particularly those undergoing allogeneic hematopoietic stem cell transplantation. Although various GVHD prophylaxis drug combinations are administered in clinical settings, previous studies have primarily focused on monotherapies or limited drug combinations. Methods : We analyzed data from the U.S. Food and Drug Administration Adverse Event Reporting System for patients receiving GVHD prophylaxis drugs between January 2004 and March 2024. Efficacy was evaluated based on the recorded occurrence or nonoccurrence of GVHD following the administration of prophylactic drugs. Drug combinations were compared using the reporting odds ratio (ROR) and adjusted ROR (aROR), which were calculated through univariate and multivariate binomial logistic regression analyses, respectively. The aROR controlled for differences in patient backgrounds. Results : This study identified 10 GVHD prophylaxis drug combinations with aROR values significantly less than 1, indicating high effectiveness, and 13 combinations with aROR values significantly greater than 1, representing low effectiveness. Conclusions: The results demonstrated that certain GVHD prophylaxis drug combinations, particularly those including cyclosporine, may be relatively ineffective. However, avoiding cyclosporine is not always feasible in clinical settings, where treatment plans must be tailored to each patient. To address this issue, the study also identified cyclosporine-containing drug combinations that exhibit high efficacy. These findings could help inform the development of personalized treatment strategies for GVHD prophylaxis and thus improve outcomes in patients undergoing allogeneic hematopoietic stem cell transplantation.